GAMBARAN SIKAP REMAJA TENTANG SEKS PRANIKAH DI SMA N 2 CILACAP KABUPATEN CILACAP TAHUN 2010 - Khosidah, Amik; Angkati, Siti (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2011)
Adolescence is a period when individuals became interested in issues of sexuality. Teenagers are expected to remain capable of sexual intercourse which is positive. Adolescents with positive social activities will be spared from premarital sexual behavior proscribed by the norms of society and religions. Objective research to know the description of adolescent attitudes about premarital sex in SMA N 2 Cilacap. Type of Research descriptive that is objective with cross sectional approach. The subject of this study is students' class X and XI by the number of respondents 84 people taken by cluster random sampling. Collecting data using questionnaires. Analysis of the data used is univariate (the percentage calculation). Results research of the 84 respondents, univariate analysis: gender-siswinya the majority of students are as much as 53.57% permpuan. Based on the age of < 17 years is 42.86%.³17 years were 57.14% while for the age  Based on adolescent attitudes about premarital sex is pretty good percentage of 55.95%, both as much as 30.95%, 13.10% were unfavorable. Conclusion research Adolescents in High School N 2nd North Cilacap Cilacap District 2010 has a good attitude is as much as 55.95%.  Suggestion research for the respondents of this research is expected to provide an input in expanding the knowledge of adolescents on reproductive especially about sex so that teenagers do not fall in premarital sexual intercourse.   Keyword: Attitude of teenagers, Premarital sex